(untitled) (Conferencea, 2022)
A physical problem in educational practice is usually called a small problem, which is generally solved with the help of logical conclusions, mathematical operations and experiment based on the laws and methods of physics. In essence, in physics classes, every question that arises in connection with the study of educational material is a task for students. Active goal-directed thinking is always problem solving in the broadest sense of the word